A Hash-Based Fast Image Encryption Algorithm - Han, Ruifeng (Wireless communications and mobile computing, 2022)
Many specialists and academics have recently become interested in the security of digital images in applications for the Internet of Things. Hash-based digital image encryption algorithms with high unified average changing intensity (UACI>30.96 percent) and only one pixel difference from the plain image would therefore adjust plenty of the pixels in the cipher image and have indeed been suggested to maintain the protection of images in the Internet of Things (NPCR>98.77 percent). Theoretical study and simulation results show that the suggested approach can fix these issues while retaining all the advantages of the original. The proposed image encryption algorithm has important application value for strengthening the security of the Internet of Things.